PRIMARY SURGERY VERSUS CHEMORADIOTHERAPY IN PATIENTS WITH STAGE III-IV ORAL SQUAMOUS CELL CARCINOMA - Kravets, O.V.; Protsyk, V.S.; Burtyn, O.V.; Khlynin, O.V.; Gurianov, V.G. (World of Medicine and Biology, 2019)
The paper offers a comparative analysis of the treatment outcomes in patients with stages III-IV resectable oral squamous cell carcinoma. The overall and disease-free five-year survival rates in individuals who had undergone primary surgery with adjuvant radiotherapy (RT) chemoradiotherapy (CRT) were 55.4% and 59.6%, respectively, whereas in patients receiving definitive CRT, they were 18.9% and 15.2%. The comparison of the overall and disease-free survival curves revealed a statistically significant ((p